2014
DOI: 10.1038/srep04481
|View full text |Cite
|
Sign up to set email alerts
|

Active transport of vesicles in neurons is modulated by mechanical tension

Abstract: Effective intracellular transport of proteins and organelles is critical in cells, and is especially important for ensuring proper neuron functionality. In neurons, most proteins are synthesized in the cell body and must be transported through thin structures over long distances where normal diffusion is insufficient. Neurons transport subcellular cargo along axons and neurites through a stochastic interplay of active and passive transport. Mechanical tension is critical in maintaining proper function in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 46 publications
(82 reference statements)
2
64
0
Order By: Relevance
“…In the complex intracellular environment, the active transport along microtubules has a values ranging from 1.4 to 2 (53). Whereas some biological studies also used the a value of 1.4 as a criterion for classification (54,55), an a value of 1.7 was used in a microfluidic experiment (36). In the same report, the criterion of Df % 0.1 was found suitable to achieve sufficient discrimination between active and passive motion (36).…”
Section: Trajectory Segmentation and Classificationmentioning
confidence: 96%
See 1 more Smart Citation
“…In the complex intracellular environment, the active transport along microtubules has a values ranging from 1.4 to 2 (53). Whereas some biological studies also used the a value of 1.4 as a criterion for classification (54,55), an a value of 1.7 was used in a microfluidic experiment (36). In the same report, the criterion of Df % 0.1 was found suitable to achieve sufficient discrimination between active and passive motion (36).…”
Section: Trajectory Segmentation and Classificationmentioning
confidence: 96%
“…In this study, we demonstrate an integrated trajectory analysis tool that adopts a combination of analytical strategies (34)(35)(36)(37)39) and classification parameters (MSD scaling exponent (53)(54)(55)(56), directional persistence (36,57), and confinement index (37,58)) in achieving effective segmentation and classification of both simulated and real-world trajectories. Our algorithm has achieved 81% accuracy in classifying segments along simulated 3D trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…In living cells it has been reported that force application fluidizes the cell mechanical properties [110] as measured by magnetic twisting cytometry. Direct measurement in living cells is sparse, however some studies have shown that applied deformation may also lead to decreased cytoplasmic resistance [111,112]. And metabolic activity was shown to fluidize the cytoplasm and facilitate motion of larger components in bacteria cells [113].…”
Section: Softeningmentioning
confidence: 99%
“…1, 2 Today we know that mechanical forces or tension are involved in the formation of the cortical landscape folding, 3 in neuronal cell morphology, 4, 5 in neurite or axonal outgrowth, 610 in synaptic functioning, 1, 11 and in signal transduction 12, 13 through mechanically activated ion channels. 14, 15 A majority of these results are derived from in vitro experiments, where the mechanical stimulus was externally positioned.…”
Section: Introductionmentioning
confidence: 99%
“…14, 15 A majority of these results are derived from in vitro experiments, where the mechanical stimulus was externally positioned. Applying external forces through glass micropipettes, 5, 16, 17 magnetic/optical tweezers, 1821 or stretchable cell platforms, 6, 11, 22 impart mechanical bending, compression, or expansion on the cell plasma membrane. Within this context it was reported that stretching axons resulted in faster accumulation of synaptic vesicles at the growth cone compared to un-stretched neurons.…”
Section: Introductionmentioning
confidence: 99%